KESENJANGAN AKSES PENDIDIKAN DIGITAL ANTARA WILAYAH PERKOTAAN DAN PEDESAAN DI INDONESIA - Muhammad Kurniawan (PT. Habe Cendekia Utama, 2025)
Digital education transformation in Indonesia is progressing rapidly but remains plagued by disparities in access between urban and rural areas, particularly the 3T (United Territories) that face limitations in infrastructure, devices, and digital literacy. This study aims to analyze the general picture of digital education access, identify the factors causing the disparity, and assess its impact and strategies for addressing it on equitable distribution of national education quality. The approach used is descriptive qualitative through literature review and content analysis of official government reports, statistical data, and scientific articles from 2017–2025 relevant to the issues of educational digitalization, the urban-rural gap, and the Merdeka Belajar policy. The results show that the expansion of ICT infrastructure, the Digitalization of Learning program, and various public-private partnerships have increased access to and utilization of technology in many educational institutions. However, disparities in internet access, device ownership, and teacher-student digital competency remain high in 3T (United Territories) regions, impacting the quality of learning, the achievement of 21st-century competencies, and the socioeconomic opportunities of students. Research emphasizes the importance of a systemic approach that integrates infrastructure strengthening, digital literacy enhancement, and multistakeholder governance and collaboration to ensure digital education transformation truly promotes equity in education in Indonesia.